Self-efficacy, burnout and teacher psychological well-being from positive psychology: an approach with structural equations - Rodríguez Chávez, Luis (2024)
The aim of the present research was to evaluate the effect of self-efficacy and burnout on psychological well-being, the latter conceived from the PERMA model of positive psychology. Therefore, we first sought to examine the composition of the dimensions of each of the aforementioned variables and then to assess the predictive capacity of self-efficacy on burnout, as well as the effect of these two variables on well-being. A non-experimental and cross-sectional research was proposed where 1135 preschool, elementary and high school teachers working in Gran Caracas (Venezuela) participated intentionally, being predominantly women (88%) with an average age of 45 years. The following questionnaires were applied: PERMA profiler, teacher burnout scale and the brief scale of teacher self-efficacy. By means of a structural equation model analysis, good fit indices were obtained for the proposed model (CFI = .98, GFI = .99; TLI = .97; RMSEA = .05; SRMR = .05) as well as measurement (λ > .30), specifically, teacher self-efficacy predicts burnout (γ = .79; p < .01) and the latter predicts psychological well-being (γ = .66; p < .01); however, self-efficacy is not a direct predictor of well-being. Thus, the role of teacher self-efficacy as a protective factor for burnout, and the negative effect of burnout on psychological well-being conceived from positive psychology, are evidenced. Based on these results, some recommendations for future research are made.